Managing gigabytes compressing and indexing documents and images - Witten Ian H; Bell Timothy C; Moffat Alistair (San Francisco Morgan Kaufmann, 1999)
It covers the latest developments in compression and indexing and their application on the Web and in digital libraries. It also details dozens of powerful techniques supported by mg, the authors' own system for compressing, storing, and retrieving text
Keywords: Data compression(Telecommunication); Document imaging systems; Image processing-digital techniques; Information retrieval; Text processing(Computer science)